Analisa Penempatan Program Keahlian dan Praktek Kerja Industri Terhadap Kesiapan Kerja Siswa Kelas XII Di SMK Negeri 6 Kota Jambi - Yudha, Redi Indra; Yanto, Ferry (Universitas Batanghari Jambi, 2024)
This research aims to understand and knowledge about the analysis of skills program placement and Industrial Work Practices (Internship) on student work readiness at SMK Negeri 6 Jambi City. The research method used in this research is a qualitative method using descriptive analysis techniques. The research results show that evaluation of learning during Prakerin can contribute and provide additional information for the development of vocational school skills programs, expanding subject matter, increasing students' interests and talents, as well as their future readiness in entering the real world of work.